1999
DOI: 10.1128/jb.181.2.577-584.1999
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli RcsA, a Positive Activator of Colanic Acid Capsular Polysaccharide Synthesis, Functions To Activate Its Own Expression

Abstract: Capsule (cps) gene expression in Escherichia coli is controlled by a complex network of regulators. Transcription of the cps operon is controlled by at least two positive regulators, RcsA and RcsB. We show here that RcsA functions to activate its own expression, as seen by the 100-fold-increased expression of arcsA::lacZ transcriptional fusion in strains with high levels of RcsA protein, either due to a mutation inlon or due to overexpression of RcsA from a multicopy plasmid. Expression of the rcsA::lacZfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…5; Wehland et al, 1999). Ebel and Trempy (1999) reported that E. coli RcsA activates its own expression. This activation is potentiated by RcsB.…”
Section: Discussionmentioning
confidence: 99%
“…5; Wehland et al, 1999). Ebel and Trempy (1999) reported that E. coli RcsA activates its own expression. This activation is potentiated by RcsB.…”
Section: Discussionmentioning
confidence: 99%
“…Besides autoactivation (Ebel and Trempy, 1999), rcsA was activated by GadE (Hommais et al, 2004) and gadE was one of the 48 genes controlled by RpoS (Patten et al, 2004; Table 1). The crucial DNA-binding regulator for Rcs regulon is RcsA together with RcsB (Ebel and Trempy, 1999). Although rcsB did not change, the expression of rcsA showed a 3.5-fold increase during carbon limitation.…”
Section: Uncovering Gene Regulation Strategy At a Genomewide Scalementioning
confidence: 99%
“…Our results suggest that H-NS could initiate a new kind of regulation by specifically modulating the expression level of those regulators. Moreover, the effect of H-NS on genes of the colanic acid operon could be mediated by the increased expression of their activator-encoding gene, rcsA (Ebel and Trempy, 1999), in the hns mutant (Table 1). This suggests that H-NS plays an indirect role in the regulation of many genes identified in this study and further supports a high position of H-NS in the regulatory hierarchy of bacterial physiology.…”
Section: Percentage Survival Bmentioning
confidence: 99%